2006
DOI: 10.1016/s0022-5347(06)00329-6
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of the Cryptorchid Testis—Can It be Salvaged?

Abstract: This series clearly demonstrates poor rates of surgical salvage, which we mainly attribute to delays in parental response and in primary physician referral to the hospital. Parents, who have a pivotal role in early diagnosis, were usually unaware of this urological emergency, and some were surprisingly unaware of the presence of cryptorchidism. By increasing the awareness regarding this entity among members of the medical community and parents, we hope that torsion of the cryptorchid testis (literally, "hidden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 14 publications
3
49
0
3
Order By: Relevance
“…In the last 5 decades, the appropriate operation age of UDT was earlier than that in the past, but the incidence of UDT torsion is similar, perhaps due to increased premature birth in the same period [2]. However, it was proposed that UDT torsion is in fact more common than what was previously reported [5].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the last 5 decades, the appropriate operation age of UDT was earlier than that in the past, but the incidence of UDT torsion is similar, perhaps due to increased premature birth in the same period [2]. However, it was proposed that UDT torsion is in fact more common than what was previously reported [5].…”
Section: Discussionmentioning
confidence: 95%
“…Epidemiological studies have shown that UDT and hypospadias are risk factors for testicular torsion, canceration, and male infertility [2]. In the past, the study on UDT mainly focused on infertility and testicular tumors, which may be noted only much later in the adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…Cet examen est largement recommandé dans la littérature. Dans les cas typiques, il révèle un testicule tuméfié avec absence de vascularisation 3,12 . Cet examen complémentaire ne doit en aucun cas retarder l'exploration chirurgicale qui seule pourra sauver le testicule.…”
Section: Les Torsions Sur Testicules Cryptorchidesunclassified
“…La majorité des auteurs recommandent la fixation systé-matique du testicule controlatéral 3,12,14 . Le taux de préservation du testicule tordu en position scrotale varie entre 20 et 92 % selon les séries 12 .…”
Section: Les Torsions Sur Testicules Cryptorchidesunclassified
See 1 more Smart Citation